PHYSICAL STABILITY TEST AND ETHANOL CREAM IRRITATION TEST OF Moringa oleifera L. - Nining Sugihartini; Zainab Zainab; Aji Pamungkas (JIIS: Jurnal Ilmiah Ibnu Sina, 2021)
The development of topical dosage forms of Moringa leaf extract cream has been carried out because of its properties that can moisturize the skin. A pharamceutical preparation must meet the requirements of stability and non toxic. The study aimed to determine the effect of variations un the concentration ethanol extract cream of Moringa leaf of physical stability and irritability.